Population Activation Service Through Digital Civil Identification App - Mutaqin, Fatwa; Kurniawan, Angga; Tri Andoyo, Syuban; Khumayah, Siti; Wulandari, Sri (Asian Journal of Social and Humanities, 2024)
Digital population identity is a government innovation for the digitization of population documents as stated in the Minister of Home Affairs Regulation No. 72 of 2022 concerning standards and specifications for hardware, software and electronic identity card forms as well as the implementation of digital population identity. This study describes the quality of population activation services through the IKD application. The type of research used is empirical which is descriptive with a qualitative approach, primary data research data sources and secondary data. Data collection techniques through observation, interviews and documents. Data analysis techniques use data reduction, data recitation and conclusion research. The quality of service in this study uses the theories of Parasuraman, Zeithaml, and Berry (2013:23), namely tangibles, reability, responsivess, assurance and empathy. The result of this research is that the quality of IKD services is not optimal, as seen from the tangibles dimension (realized) in the infrastructure and facilities of IKD services and there are still obstacles, namely in the IKD activation procedure due to limited public knowledge.